Identification of genetic mutations of cutaneous squamous cell carcinoma using whole exome sequencing in non-Caucasian population. Issue 2 (May 2022) - Lee, Soo Young; Lee, Minho; Yu, Dong Soo; Lee, Young Bok
Abstract: Background: Cutaneous squamous cell carcinoma (cSCC) is the second most common nonmelanoma skin cancer worldwide. Recent studies have reported several genetic mutations in development of cSCC such as TP53, HRAS, and NOTCH1 . Whole-exome sequencing (WES) of cSCC has not been reported in East Asian populations. Objective: We aimed to investigate genetic mutations of cSCCs in Korean patients by WES. Methods: cSCCs and paired peripheral blood samples were obtained from 19 Korean patients who underwent wide excision on the cheek from 2016 to 2020 and divided into moderate to poor-differentiated (MP-D) cSCCs (n = 9) and well-differentiated (W-D) cSCCs (n = 10) according to the histopathological evaluation. WES was performed for analysis of genomic mutations of cSCCs. Results: The mean total mutation burden of MP-D cSCCs was higher than W-D cSCCs. Also, we observed proportionately more driver mutations in MP-D cSCC than W-D cSCC groups. CSMD3, COL22A1, FMN2, and ASXL3 mutations are highly frequent than the results of previous reports in cSCC of Caucasians. Conclusion: These results may aid in further our understanding of the complex process underlying tumorigenesis of cSCC in non-Caucasian populations. Highlights: The mean total mutation burden of MP-D cSCCs was higher than W-D cSCCs. More driver mutations were observed in MP-D cSCC than W-D cSCC groups. CSMD3, COL22A1, FMN2, and ASXL3 mutations are highly frequent than the results of previous reports in cSCC of Caucasians.